TRIAGEM FITOQUÍMICA E AVALIAÇÃO DA ATIVIDADE ANTIOXIDANTE DE Cedrela fissilis VELL. (MELIACEAE) - ADRIANO, Bruno Braga Nogueira,; SILVA, Cristiane Aparecida Rosa Pavera,; CRUZ, Sorraylla Layanny Alvarenga,; ILVA, Ana Francisca Gomes,; FEITOSA, Bruno Henrique, (ANAIS DO ENIC, 2022)
-